For a history of childhood and of his education in contemporary Italy. Interpretations and perspectives of research (Bilingual Edition: English/Italian) - Roberto Sani (Cadernos de História da Educação)
Abstract The history of childhood and childhood education has experienced, in Italy, a real development only in the last forty years. The reason of such a delay is due to several factors. First of all, the prevalence in the Italian historiography, until the seventies, of the ethical-political matrix derived from Hegel's idealism, which wasn't avoided not even by the Marxist historians. Secondly, the serious delay with which the historical-pedagogical research - for a too long period of time confined within the narrow limits of the history of pedagogical doctrines and of the philosophical theories of education- has developed its own cultural and epistemological identity and autonomy and the methodologies and conceptual frameworks typical of the historiographical research. This paper is based on the awareness that the history of childhood - for the «elusive» character of the object to be studied and for its being placed in a border area between different sectors and fields of research - involves a complex and structured approach, able to allow different levels of analysis and reading; thus requiring the contribution of various historiographical skills in an interdisciplinary perspective (social history, that of institutions and educational practices, but also the history of mentalities, cultural processes, etc.). It consists of two separate parts, and is meant to focus on the previous investigations, on the current situation and on the future developments in this field of research. In the first part, after having provided an extensive review of the research and studies on the history of childhood and on childhood education published in Italy in the last decades, the Author analyzes certain issues relating to the methodological and historiographical organization of these studies. In particular, he focuses on some themes of the history of childhood and its education little or not at all investigated by scholars, as well as on the trend typical of several papers appeared in the last decades to define and interpret the historical events of childhood on the basis of an approach using «models», derived, a little bit uncritically, from the social sciences, which does not seem to adequately take into consideration the complexity of the educational and cultural-historical processes that have affected Italy. In the second part of the work, in order to facilitate the expansion and the refinement of the historical investigation on this issue, the Author aims to illustrate the importance of certain research and of some sources still little or not used by scholars to analyze the history of his childhood and education in contemporary Italy (XIX-XX centuries). For what concerns this aspect, a special attention is given to the role - still largely to be explored - of the Catholic Church in the support and in the religious and civil education of childhood, as well as in the construction of a certain children imagination in the adult world.